2001
DOI: 10.1007/s003440010038
|View full text |Cite|
|
Sign up to set email alerts
|

Occurrence of Gibberellins in Vascular Plants, Fungi, and Bacteria

Abstract: The occurrence of GA1 to GA126 in vascular plants, fungi, and bacteria is listed. The data are discussed with reference to criteria for identification and to the frequency of occurrence of GAs in vascular plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
159
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(166 citation statements)
references
References 0 publications
0
159
0
7
Order By: Relevance
“…Occurrence, biosynthesis and biological activity GAs have been detected in a range of terrestrial vascular plants, including ferns and gymnosperms, and are also present in some fungi and bacteria (MacMillan 2002). Compared with auxin, our understanding of GA synthesis is markedly superior.…”
Section: Gibberellinsmentioning
confidence: 99%
“…Occurrence, biosynthesis and biological activity GAs have been detected in a range of terrestrial vascular plants, including ferns and gymnosperms, and are also present in some fungi and bacteria (MacMillan 2002). Compared with auxin, our understanding of GA synthesis is markedly superior.…”
Section: Gibberellinsmentioning
confidence: 99%
“…Gibberellin (GA), another growth regulator, promotes plant growth in higher plants, but is also produced by fungi and bacteria (MacMillan 2001). It is presumed that GAs in fungi and bacteria are secondary metabolites that act as signaling factors to establish the interaction with host plants.…”
Section: Introductionmentioning
confidence: 99%
“…However, based on the prevalence of 2b-hydroxylated GAs in many plant species (MacMillan, 2002), the most widespread mechanism for GA inactivation seems to be via 2-oxidation, in which the diterpene backbone is hydroxylated at C-2b and, in some cases, further oxidized to a ketone (Sponsel and Macmillan, 1978;Thomas et al, 1999), which undergoes nonenzymatic rearrangement to form a so-called GA catabolite. Biochemical characterization of the enzymes responsible for 2b-hydroxylation showed that, like the GA 20-oxidases and GA 3-oxidases, they belong to the soluble 2-oxoglutarate-dependent dioxygenase class (Griggs et al, 1991).…”
Section: Introductionmentioning
confidence: 99%